Unfinished Agenda: Understanding Poverty and Determination of Targets through the Data Collection of the Poor Population (Study Program of Jalin Matra PFK in Probolinggo District, East Java) - Nunuk Dwi Retnandari; Astri Tantrina Dewi (Iapa Proceedings Conference, 2019)
Many programs have been designed and implemented to get the population out of poverty. However, the results achieved are not always satisfactory. Probolinggo District has implemented the Jalin Matra PFK as a program specifically designed for women to be free from their poverty conditions. However, this program still produces the same output, where women poor population is not much reduced. An in-depth investigation of the understanding of the concept of poverty and the data collection system that was carried out found the cause of the failure of the PFK program. The definition of poverty described in Indonesia is not always in accordance with the local concept of poverty. Besides, the definition of poor program recipients is poor population decile 1. On the other hand, the purpose of the program is empowerment. Therefore, the initial definition of this program is not quite correct. The inaccuracy of this definition has implications for incorrect data collection. It is also exacerbated by the implementation of an integrated data collection system that is distorted by several things. Defining different productive age groups between agencies is the first distortion. The difference in authority in determining the number of program recipients is the subsequent distortion. Community and local officials’ perceptions of poverty based on cultural poverty also distort the data verification process. As a result, an error occurred in the database as a basis for program implementation.